IMPROVING TIME PRODUCT LAUNCH WITH BALANCED SCORECARD AND KEY PERFORMANCE INDICATORS IN PT. DIPA PHARMALAB INTERSAINS - Gabriel Mardi Bunawan; Moh. Kiki Iqbal; Gerald Ariff (Journal of Business Strategy and Execution, 2011)
As a pharmaceutical company, DPI has implemented many management improvement systems such as 5S, ISO, BSC and Kaizen. Starting in 2005, DPI implemented 5S to improve its filing system and continued with ISO 9001 for management quality improvement. In 2007, DPI received ISO certification and Balanced Scorecard (BSC). Despite long implementation time, the BSC system has not run well because of poor understanding and weak top down enforcement. Although DPI had achieved good performance without BSC, its top management never really knows what the current situation of DPI’s business is. Implementing BSC at that time still couldn’t answer the question. On the other hand, implementing BSC was a kind of waste time of and money with very minimum impact on top management decision monitoring of DPI’s business processes DPI’s BSC has been modified several times. The last version was implemented in 2011 with a breakdown of KPIs down to individual level. Still this last version and KPIs are not running well especially in quality aspect. With this new version, top down strategic map and KPIs seem to run well but the horizontal KPI are not yet established. With this situation every department only have guidance in vertical line and don’t care about other departmental achievement. One sample of this situation could be seen on launching new products. This situation has to be improved using BSC and KPI.